Knowledge of Health Hazards and Perception of Prevention Amongst Females Exposed to Biomass Fuel and Gas/Electricity Fuel in A District of Bangladesh (Anwer Khan Modern Medical College Journal, 2013)
Indoor air pollution from biomass smoke is now regarded as public health hazard in the developing world, where more than two billion people still rely on the use of solid biomass fuels such as, dung, wood, crop residue and coal for cooking daily meals and heating homes. A crosssectional    study was designed and conducted from March to June 2007, in Madla, a rural area,  and in Thanthania, an urban area, under Bogra District of Bangladesh, to see and compare the prevalence of respiratory disease among female biomass fuel users and gas/electricity fuel users.    A total of 103 females from the rural households meeting the defined enrollment criteria for biomass fuel group were selected purposively as cases, while 101 females from the urban households meeting the defined eligibility criteria for controls were included in gas/electricity fuel group. The participants were interviewed on a semi-structured questionnaire. Nearly 70% of the biomass fuel users used wood for the daily cooking and heating purposes, 64% leaves, 31.1% cow dung, crop residue 30.1% and 7.8% saw-dust. The biomass group exhibited a significantly higher frequency of respiratory problem (16.5%) compared to their gas/electricity counterpart (5%). The findings revealed that, 67.5% of the biomass group complained of eye problem followed by cold 36.1%, headache 33.8%, cough 13.9% and difficulty in breathing 11.1%. The respondents of gas/electricity group also complained about same health hazards but    they were less aware of the problems. Both the group had fairly comparable level of perception of prevention of hazards of biomass fuel (p>0.05), except that a significantly higher proportion of biomass group (12.2%) told that the problem could be avoided by using kerosene stove    compared to the gas/electricity group (1.2%). DOI: http://dx.doi.org/10.3329/akmmcj.v4i1.13680 AKMMC J 2013; 4(1): 20-24